CLINICAL CASE: CANCER OF THE BODY OF THE UTERUS WITH THE RETURN OF THE DISEASE AFTER 12 YEARS. - N.E. Atakhanov; V.K. Yahyayeva; U.I. Esonturdiev; N.I. Tursunova; I.S. Abdinazarova (Scholar Express Journals, 2022)
The article presents a clinical case of cancer of the uterine body with the return of the disease after 12 years. The clinical picture of the disease was dominated by pain and the presence of postoperative hernia. After a thorough diagnostic examination and preliminary preparation, the patient was co-operated in the department of the oncogynecology of the Tashkent City Branch of the Republican Specialized Scientific and Practical Medical Center of Oncology and Radiology. The paper analyzes the reasons for the return of the disease after 12 years, considers options for preventing the recurrence of the disease. These data can help in the management of patients with this pathology and improve disease-free survival of patients.
Keywords: Cancer Of The Uterine Body; Metastasis; Incisional Hernia; Undifferentiated Carcinoma.